Analisis Penerapan Time-Driven Activity-Based Costing sebagai Pembanding Metode Tradisional dalam Penentuan Harga Kamar dan Profitabilitas pada Hotel XYZ - Zahra Amalia; Muhammad Nur Afif; Maria Magdalena Melani (Balance : Jurnal Akuntansi dan Bisnis, 2026)
This study aims to compare the traditional costing method with Time-Driven Activity-Based Costing (TDABC) in determining room costs and evaluating profitability at Hotel XYZ. The research uses a descriptive quantitative approach with a case study method, utilizing operational cost data, service activities, time estimates, and room occupancy rates. The results show that the traditional method causes cost distortions in the form of overcosting and undercosting due to uniform cost allocation. In contrast, TDABC calculates room costs based on activity time consumption and capacity cost rates, resulting in more accurate and representative cost information. TDABC also identifies differences in capacity utilization and profitability among room types more clearly. The study concludes that TDABC provides a more precise and relevant costing system that supports managerial decision-making in pricing strategies and improves sustainable profitability management in the hotel industry.